Gender, Authority and the Image of Queenship in English and Scottish Ballads, 1553–1603. - HYDE, JENNI (History, 2020)
This article uses contemporary ballads to show that dynastic right was of central importance to the popular view of the accessions of Mary I and Elizabeth I, as well as that of the foreign king James VI when he acceded to the English throne in 1603. It challenges our view of Tudor iconography by showing that although popular songs were not afraid to tackle the gender implications of queens regnant, the popular image of Elizabeth I was not centred on her femininity. The article compares the positive English view of Mary I's femininity with negative portrayals of Mary Queen of Scots in Scotland, while suggesting that the issue of femininity was not raised in ballads about Elizabeth I because her half‐sister had already normalised the idea of a woman on the throne.